Description of New Miridae and Tingidae Species (Hemiptera: Heteroptera) and New Records from Southern Turkey - Çerçi̇, Bariş; Gorczyca, Jacek; Koçak, Özgür (Zootaxa, 2021)
In this study, Fulvius anatolicus Çerçi & Gorczyca sp. n., Orthotylus (Pinocapsus) kmenti Çerçi & Koçak sp. n. (Miridae) and Lasiacantha karamanensis Çerçi & Koçak sp. n. (Tingidae) are described from Turkey. Dorsal habitus of each species, male and female genitalia of F. anatolicus sp. n. and male genitalia of O. (P.) kmenti sp. n. are illustrated. Differential diagnostic features between closely related species and the new species are given. Additionally, Hallodapus costae (Miridae) and Tempyra biguttula (Rhyparochromidae) are recorded from Turkey for the first time. Latter is a new alien species for the fauna of Turkey.